Foundations of Community Engagement: A Series for Effective Community-Engaged Research - Bryan Johnston; Leslie Ruffalo; David Nelson; Sarah O'Connor; Staci Young (MedEdPORTAL, 2023)
Introduction Medical students lack systematic exposure to community engagement. Community-engaged research (CEnR) is an effective approach to improve community health, and community-engaged physicians are better attuned to the community context of their patients' health and well-being. The Medical College of Wisconsin (MCW) Office of Community Engagement began offering the educational series Foundations of Community Engagement in 2021 to meet this need. Methods We developed and implemented a four-session series for medical students at MCW and the University of Nebraska Medical Center. A 1-hour session on the foundations of CEnR was held for all learners. Three 1-hour sessions dove deeper into CEnR principles for a self-selected cohort. These small-group sessions involved discussion between faculty and community partners and facilitated small-group discussion. Students completed evaluations after each session. Results A total of 160 students participated in the introductory session; 36 took part in the follow-up series. Survey response rates varied from 38% to 67% for each session. Overall, 87% of students in all sessions felt their session was worthwhile, with 85% of large-group and 96% of small-group respondents reporting they learned something they would use in their practice or profession. Qualitative responses included appreciation for addressing a curricular gap and desire for more time and more sessions to continue discussions. Discussion The program was effective at stimulating medical student self-reported gains in skills, attitudes, and future intentions regarding CEnR in an efficient manner. Effective programs that transfer positive CEnR skills and attitudes to future physicians can promote CEnR within academic medicine.